Alternative Tourism in Wonosalam - I Dewa Gde Satrya (Politeknik Pariwisata Makassar, Indonesia, 2022)
Alternative tourism and ecotourism find their relevance in changing travel patterns in the next normal era. Both enable tourism trips that have a positive impact on the growth of the quality of life of tourists and hosts, as well as the quality of the environment and cultural conservation that are the destinations of travel. Ecotourism is a way for alternative tourism to be increasingly recognized and become the answer, when tourist travel turns to a small scale, considering the capacity of tourist destinations and the welfare of local communities. This article is based on qualitative data obtained through interviews and indepth observations related to the implementation of alternative tourism managed by local communities as well as Forest Conservation Groups in ecotourism destinations in Mendiro Hamlet, Panglungan Village, Wonosalam District, Jombang Regency, East Java Province. Wonosalam is not only known for its durian commodities but has many springs, conservation forests, and Biodiversity Parks. The purpose of this study is to describe the implementation of alternative tourism in Wonosalam. This study concludes that the concept of alternative tourism finds its relevance to ecotourism practices in Wonosalam through observation of springs, jungle tracking, river crossings, birdwatching which is done on a small scale, and the attraction of tourist villages located on the border of conservation forests. The owners